Making the most of the Chicago Benchmarking Collaborative - Shumate, Michelle, (SAGE Knowledge. Cases., 2018)
The Chicago Benchmarking Collaborative began in 2009 as a partnership of five agencies focused on education and other human services in the Chicago area. Traci Stanley, director of quality assurance for the Chicago-based nonprofit Christopher House, was preparing for the October 2016 meeting of the Chicago Benchmarking Collaborative. Although the data suggested all CBC agencies had improved on the parent engagement measure, the magnitude of improvement varied among the agencies. The challenge for Stanley and fellow CBC managers preparing for the fall meeting was not only to understand sources of variation, but also to ensure members shared ideas for actionable best practices in line with the mission of enhancing the impact of all CBC agencies across service areas.